The legal challenges of social media - Mangan, David; Gillies, Lorna E. (Elgar law, technology and society, 2017)
Social media offers a platform for individual self-expression and the sharing of information. However, social media issues are boundless, permeating distinct legal disciplines. The law has struggled to adapt and for good reason: how does the law regulate this medium over the public/private law divide? This book engages with the legal implications of social media from both public and private law perspectives and outlines how the law has endeavoured to adapt the existing tools to social media. The expert contributors explore a range of ideas to investigate the intersection between law and social media and they provide an insight into the challenges the legal community currently face. This collection explores key topics such as public and private law implications, the gap between the lay and legal understandings of social media, the conflict of laws regarding social media and the individual rights associated with social media.-